The collapse of the wave function as the mediator of free will in prime neurons - Loboguerrero, Diego A. (Frontiers in Neuroscience, 2025)
In our current view of reality, free will hangs on two opposing forces. On one side, we have determinism, which states that everything is already determined by our inner constituents, the atoms and molecules that form our bodies. On the other side, we have quantum mechanics and its view that everything in the quantum world is inherently random and probabilistic. None of these perspectives gives rise to the phenomenon of what we call free will, but here in this article, we provide an underlying mechanism for how free will should operate in our world. We propose that the collapse of the wave function is responsible for determining our free will in prime neurons. The collapse of the wave function is the process by which a particle passes from a state of superposition or being in several places at the same time to a definitive state with clearly established properties. Prime neurons are a class of neurons that are responsible for initiating a thought process or an action in our brains. But for this to operate, the collapse of the wave function must not act on regular matter, for that would yield a purely random result. We need a new and hypothetical particle, for which we have placed the term “soul/spirit particle.” This soul/spirit particle has very specific features, as we have discussed in this article, and we have provided a mathematical model to explain its interaction with our inner physiology.